Detail specification for multi-contact rectangular electrical connectors with moulded bodies for d.c. and low frequency applications. Unsealed with end guides or jackscrew couplings and non-removable solder contacts. Full assessment level. (15th October 1981) - British Standards Institution,
No abstract available